Long term survival of advanced hepatoid adenocarcinoma of lung secondary to idiopathic pulmonary fibrosis: a case report - Wang, Xiaoli; Wei, Nan; Yang, Huizhen; Wang, Xiaoyan; Zhang, Xiaoju; Zhang, Qianqian (Frontiers in Oncology, 2025)
BackgroundAlpha-fetoprotein (AFP)-producing hepatoid adenocarcinoma of lung (HAL) is a rare type of lung cancer, with its characteristics being not yet fully clarified. We recently encountered a case of HAL combined with idiopathic pulmonary fibrosis (IPF), which has never been reported.Case presentationA 66-year-old man consulted our hospital with a chief complaint of cough. Chest computed tomography (CT) revealed multiple nodules measuring from 8mm to 20mm in diameter located in bilateral lung, along with an enlarged left hilar lymph node. CT-guided percutaneous lung biopsy confirmed the diagnosis of AFP-producing primary HAL combined with IPF. Systemic treatment according to guidelines for advanced non-small cell lung cancer resulted in a long-term survival.ConclusionsThis case report documents the first occurrence and prognosis of AFP-producing HAL in a patient with IPF. The long-term survival brought by the diagnosis and treatment model in our case may provide significant prognostic value for this rare condition.